A special introduction / David L. Uzzell - David, L. Uzzell (Faculty of Architechture , Planning & Surveying, 2011)
The launch of a new journal is always an exciting occasion. Of course, it is a very tangible sign that an area of scholarship is developing and that there is a body of work being undertaken that is of sufficiently high standard that warrants publication. It is also very auspicious, to use a word that I am very conscious has important meanings in Asian cultures. It is auspicious because it makes a statement not only about the present - and indeed past research - but it looks to the future as well. It is a statement of commitment and of confidence that this area of scholarly endeavour is important.